Uji Potensi Produksi Biogas pada Campuran Kiambang (Salvinia molesta) dan Limbah Jeroan Ikan Gabus (Channa striata) Menggunakan Batch Anaerobic Digester - Diaz Liansyah Pratama; Siti Hanggita; Agus Supriadi (Universitas Sriwijaya, 2015)
The purpose of this research is to utilize Salvinia biomass and snake head fish’s viscera waste as substrats for biogas production as a renewable energy sources by different treatment on substrate composition. This research was conducted on December 2014 until February 2015. This research used experimental method in anaerobic batch reactors with Liquid Displacement and Atomic Absorbtion methods using NaCl and NaOH solutions. The results in this research analyzed with descriptive method. The observed parameters were biogas and methane production rate and accumulation, and slurry’s parameters such as themperature, pH, BOD, COD, TS, VS, and C/N ratio. Results showed that the difference of substrates composition in reactor A produced the highest biogas and methane accumulation at 7.017 and 3.803 mL/kg slurry with the highest removal per kg slurry at 0.34 g BOD, 9.60 g COD, 47.24 g TS, 21.21 g VS. Whereas in reactor B produced the highest methane percentage at 60.73% and C/N removal at 1.23.